Vitamin D and HbA1c levels in newly diagnosed type 2 diabetes mellitus - Baligumba Ramu Kiran; Venoor Shreyas Kumar; Giri Premkumar Preeti; Venoor Ajith Kumar; Bheemappa Raja Vikas (MGM Journal of Medical Sciences)
Background: This study examined the correlation between 25-hydroxyvitamin D [25(OH)D] and glycated hemoglobin (HbA1c) levels in male and female patients diagnosed with type 2 diabetes mellitus (T2DM). Design: Hospital-based cross-sectional study. Materials and Methods: This study was conducted in the Department of General Medicine at Rajarajeswari Medical College and Hospital, Bengaluru, Karnataka, India, with the Institutional Ethics Committee approval. Each participant admitted to the hospital as an inpatient or outpatient underwent a thorough medical history review, physical examination, and relevant diagnostic tests. Vital signs, including pulse rate and blood pressure, were recorded as part of the general examination. Additionally, detailed assessments and investigations evaluated participants for potential vitamin D deficiency. Results: The mean age of participants was 59.46 ± 11.06 years, with an observed trend of increasing vitamin D deficiency with age. No significant association was found between gender and HbA1c or vitamin D levels. The average HbA1c level was 9.75% ± 2.05, while the mean vitamin D level was 23.44 ng/mL ± 8.26. A negative correlation was identified between serum vitamin D and HbA1c levels, with a correlation coefficient of −0.53 and a P value of <0.01. Conclusion: The study confirmed an association between vitamin D deficiency and elevated HbA1c levels in T2DM patients, with variations observed between male and female subjects.